Teaching at The Right Level Approach: Implementation Guide Inquiry & Cooperative Learning with Feedback on the Learning Outcomes of Students - Adam, Mukhammad Ibnu; Hanafi, Yusuf; Sagita, Ferdi Dwi (Proceeding International Conference on Religion, Science and Education, 2025)
The research aims to determine whether or not there is an influence from the results of teaching practice to improve student learning outcomes in science material on the classification of living things by implementing the learning model Guide Inquiry Learning using Kahoot.it with gifts Feedback and Cooperative Learning TGT Type (Teams Games Tournament) TaRL-based (Teaching at The Right Level). This research focuses on student learning outcomes during two cycles. The research method used is a mixed method with a research design sequential explanatory in the form of a combination of two studies in the form of qualitative and quantitative in a systematic and coherent manner. Analysis of the data used Paired Sample t-Test & test Group Pretest-Posttest To obtain quantitative data, meanwhile the data will also be described qualitatively and additional instruments will be used such as observation, interviews with teacher and student resource persons. The main instrument in research is questions pre-test and post-test. The research was conducted in the same semester at a State Junior High School in Malang City. The research subjects were 29 students in one class who had never studied the material tested by integrating the variables in the research. 1) the results show that the treatment provided in the experimental class shows that there is significant progress in student learning outcomes; 2) students are more active, able to search for information and improve their scientific literacy, increased learning outcomes from working on analytical type questions which are balanced with good understanding of concepts, and students’ collaboration & communication skills are getting better; 3) the normality test carried out shows that the data is normally distributed and the t test carried out shows the value themselves. (2-tailed) < 0.05 which indicates the influence of the variables tested with the experimental class.